PENGARUH WRITING ANXIETY DAN WRITING SELF-EFFICACY TERHADAP KEMAMPUAN MENULIS AKADEMIK MAHASISWA - Desiana Ekasari Putri; Nihlatul Falasifah (Pustakaloka, 2025)
Writing plays a crucial role in student success in college, although some individuals experience difficulties in writing coherent academic texts for scientific work. Among the challenges, anxiety and self-efficacy contribute to the writing process. This study aims to determine the effect of writing anxiety and writing self-efficacy on students' academic writing skills in nine faculties at UIN Sunan Ampel Surabaya. This research employed a quantitative approach, with a population of undergraduate students from the 2022-2024 intake. Proportional stratified random sampling was used for sampling. Data were collected using an online questionnaire and a literature review. Data were analyzed using statistical tests with SPSS version 25, including validity, reliability, normality, multicollinearity, heteroscedasticity, and multiple linear regression. The results showed that writing anxiety had a negative and insignificant effect on academic writing skills (p = 0.361 > 0.05). Writing self-efficacy had a positive and significant effect on academic writing ability (0.00 < 0.05). Simultaneously, both independent variables contributed 79.6% to students' academic writing ability. These findings indicate that writing self-efficacy significantly influences academic writing ability, while writing anxiety does not show a significant individual effect.